2008
DOI: 10.1016/j.jpainsymman.2007.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Good Death Inventory: A Measure for Evaluating Good Death from the Bereaved Family Member's Perspective

Abstract: The aim of this study was to develop a measure for evaluating good death from the bereaved family member's perspective, and to examine the validity and reliability of the assessment. A cross-sectional anonymous questionnaire was administered to bereaved family members of cancer patients who had died in a regional cancer center from September 2004 to February 2006. We measured the Good Death Inventory (GDI), Care Evaluation Scale, and an overall care satisfaction scale. A retest was conducted one month after se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
308
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 260 publications
(324 citation statements)
references
References 29 publications
11
308
0
5
Order By: Relevance
“…This suggests that clinicians and caregivers should consider the wishes and opinions of the patient and family as to what they consider a good death, and caution must be emphasised to clinicians and caregivers ensuring that their own perceptions of a good death does not bias or overpower the opinions of the patient and family. A dearth of qualitative research has been conducted in an effort to conceptualise a good death for terminally ill patients (Seale, 1991;Steinhauser et al, 2002;Tong et al, 2003;Beckstrand et al, 2006;Kehl, 2006;Rietjens et al, 2006;Miyashita et al, 2008); however, due to the complexity and vulnerability of these participants, experiences of families and caregivers on this topic tend to appear more frequently in the literature (Morita et al, 2002;Bosek et al, 2003;Teno et al, 2004;Shiozaki et al, 2005;Papastavrou et al, 2007;Sampson, 2011;Lee et al, 2013;van der Steen et al, 2013). Vig et al (2002) described good deaths as being pain free, dying in one's sleep, quickly, without suffering, and without knowledge of impending death.…”
Section: The Concept Of a 'Good Death' In Dementia Carementioning
confidence: 99%
“…This suggests that clinicians and caregivers should consider the wishes and opinions of the patient and family as to what they consider a good death, and caution must be emphasised to clinicians and caregivers ensuring that their own perceptions of a good death does not bias or overpower the opinions of the patient and family. A dearth of qualitative research has been conducted in an effort to conceptualise a good death for terminally ill patients (Seale, 1991;Steinhauser et al, 2002;Tong et al, 2003;Beckstrand et al, 2006;Kehl, 2006;Rietjens et al, 2006;Miyashita et al, 2008); however, due to the complexity and vulnerability of these participants, experiences of families and caregivers on this topic tend to appear more frequently in the literature (Morita et al, 2002;Bosek et al, 2003;Teno et al, 2004;Shiozaki et al, 2005;Papastavrou et al, 2007;Sampson, 2011;Lee et al, 2013;van der Steen et al, 2013). Vig et al (2002) described good deaths as being pain free, dying in one's sleep, quickly, without suffering, and without knowledge of impending death.…”
Section: The Concept Of a 'Good Death' In Dementia Carementioning
confidence: 99%
“…Studies have shown that preparation for death is a key factor in making the dying process more favorable for patients and their families. 32,33 Miyashita et al 33 identified 'dying in a favorite place' as a core domain in dying a 'good death.' Our patient survived approximately 4 months after diagnosis, allowing her to return to her native Germany for her waning days.…”
Section: Discussionmentioning
confidence: 99%
“…Questionnaires about the palliative care service were mailed to bereaved families in June 2007 and again in August 2007 to non-responding families. The detailed methods of the larger study have been given elsewhere [21,22].…”
Section: Participantsmentioning
confidence: 99%